Analisis Pengaruh Price, Discount, dan Free Shipping dalam Mempengaruhi Keputusan Pembelian pada Marketplace Shopee (Studi Kasus Gen Z Kotabaru) - Andriansyah; Dayat Ikhsan Hajati (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
The emergence of marketplace applications has encouraged Generation Z to take advantage of digital promotions such as discounts and free shipping to enhance their shopping experience. With their cost-conscious characteristics, these factors influence their consumptive behavior. This study aims to determine the influence of price, discount, and free shipping on the purchase decisions of Generation Z in Kotabaru Regency on the Shopee marketplace. This research is a causal associative study using a quantitative approach. The number of samples required in this study was 385 respondents, selected through non-probability sampling using a purposive sampling technique. The data were analyzed using multiple linear regression analysis. The results of this study indicate that the variables price, discount, and free shipping have a positive and significant influence on the purchase decision variable, both partially and simultaneously, for Generation Z in Kotabaru on the Shopee marketplace.